Адміністративно-правові засади взаємодії підрозділів внутрішньої безпеки Національної поліції з іншими суб’єктами забезпечення дисципліни та законності : дисертація - Володін, О. О.; Volodin, O. O.; Василенко, В. М. - науковий керівник (Харківський національний університет внутрішніх справ, 2024)
Дисертацію присвячено визначенню сутності, змісту та особливостей адміністративно-правових засад взаємодії підрозділів внутрішньої безпеки Національної поліції з іншими суб’єктами забезпечення дисципліни та законності, а також формулюванню перспективних шляхів удосконалення відповідного адміністративного законодавства. Надано сучасний погляд на розуміння взаємодії суб’єктів забезпечення дисципліни та законності як об’єкта адміністративно-правового регулювання. Виокремлено особливості взаємодії суб’єктів забезпечення дисципліни та законності як об’єкта адміністративно-правового регулювання. Доведено, що особливе місце в системі суб’єктів забезпечення дисципліни та законності посідають підрозділи внутрішньої безпеки Національної поліції. Вказано на особливості, що обумовлюють провідне місце підрозділів внутрішньої безпеки Національної поліції в системі суб’єктів забезпечення дисципліни та законності. Визначено, що категорія «напрямки взаємодії» характеризується комплексним поєднанням завдань і повноважень, які визначають спрямованість певної сумісної діяльності її учасників, що проявляється у відповідному змісті взаємовідносин. Сформовано авторське бачення сутності адміністративно-правових засобів взаємодії підрозділів внутрішньої безпеки Національної поліції з іншими суб’єктами забезпечення дисципліни та законності. Сформульовано напрями розвитку адміністративного законодавства, яке регулює взаємодію підрозділів внутрішньої безпеки Національної поліції з іншими суб’єктами забезпечення дисципліни та законності.

The thesis is devoted to determining the essence, content, and features of the administrative and legal principles of interaction between internal security units of the National Police and other subjects of ensuring discipline and legality, as well as to formulating promising ways to improve the relevant administrative legislation. A modern view of the understanding of the interaction of subjects of ensuring discipline and legality as an object of administrative and legal regulation is provided. The peculiarities of the interaction of subjects of ensuring discipline and legality as an object of administrative and legal regulation are highlighted. It has been proven that the social relations arising from the need to ensure discipline and legality are quite complex and multifaceted and also touch upon a significant number of other social relations within which there is a need for such activities by subjects authorised by the state. The author's vision of the essence of the system of subjects of ensuring discipline and legality is given. It has been found out that in addition to the subjects of ensuring discipline and legality themselves, the studied system also includes the connections that exist between them, under which it is proposed to consider the legal status of such subjects, as well as the common goal of their activities - ensuring discipline and legality within the functioning of the relevant sphere of social relations. It has been proven that the internal security units of the National Police occupy a special place in the system of subjects of ensuring discipline and legality. The features that determine the leading place of the internal security units of the National Police in the system of subjects of ensuring discipline and legality are indicated. The features of administrative and legal norms that determine the legal principles of interaction between internal security units of the National Police and other entities ensuring discipline and legality have been outlined. It has been determined that the category of “directions of interaction” is characterised by a complex combination of tasks and powers that determine the direction of a certain joint activity of its participants, which is manifested in the corresponding content of the relationship. The author’s vision of the essence of the administrative and legal means of interaction of the internal security units of the National Police with other subjects of ensuring discipline and legality was formed. The administrative and legal means of interaction of the internal security units of the National Police with other subjects of ensuring discipline and legality have been classified: 1) normative; 2) organisational and legal; 3) control and supervision; 4) preventive. It has been emphasized that the essence of assessing the effectiveness of the interaction of relevant entities, including the internal security units of the National Police, with other entities ensuring discipline and legality lies in the direct analytical work of the subject of assessment to determine the compliance of the actual results of interaction with the defined goals and objectives. Foreign experience of interaction of entities ensuring discipline and legality is analyzed, and attention is drawn to the need to adopt existing best international practices of law enforcement agencies, including in relation to ensuring control over the activities of police officers within the framework of departmental and interdepartmental interaction of entities of internal and external control. Directions for the development of administrative legislation regulating the interaction of internal security units of the National Police with other entities ensuring discipline and legality have been formulated.
Administrative and legal principles of interaction between internal security units of the National Police with the other subjects of ensuring discipline and legality
Keywords: Україна; Дисертації. Theses. Диссертации; 12.00.07; Національна поліція; підрозділи внутрішньої безпеки; дисципліна; законність; контроль; правові засади; завдання; функції; повноваження; компетенція; взаємодія; адміністративне законодавство; Ukraine; National Police; internal security units; discipline; legality; control; legal principles; tasks; functions; powers; competence; interaction; administrative legislation